Economic burden of diabetes in France between 2012 and 2017 based on French national claim database. (13th November 2019) - Denis, P; Aguadé, A; Lesuffleur, T; Pestel, L; Nicolas, M; Rachas, A; Gastaldi-Menager, C
Abstract: Background: The aim of this study is to assess the economic burden of diabetes in France based on a top-down allocation of health care expenditure, and to analyze structure and trends of expenditure between 2012 and 2017. Methods: Using information about 57 millions of individuals from the general scheme insurance database (87% of the French population), we applied algorithms based on ICD-10 diagnoses, long-term diseases, and specific treatments. All reimbursed expenditure (drugs, medical visit and other ambulatory care, hospitalization, disability/sickness benefits) were extracted for each individual. A top-down method was used to allocate expenditure to diabetes. To analyze trends, we applied the same methodology from 2012 through 2017. Results: In 2016 (results for 2017 will be available for the conference), among the 137 billion euros reimbursed, 6.8 billion (5%) were attributed to diabetes and 3.2 million people were concerned (5.5% of the population). Drugs represented the main expenditure item (31% of the average annual expenditure per patient related to diabetes), followed by nursing (18%) and medical devices (17.5%). From 2012 to 2016, the number of people with diabetes increased by 11.4% (+322 700) with an increase by 2.7%/year, the expenditure attributed to diabetes increased by 2.3%/year. The average expenditure per patient in 2016 was about €2150, slightly decreasing from 2012, mainly due to price controls on antidiabetics drugs which permits to limit expenditure growth. Conclusions: Our study shows the high economic burden of diabetes in France with a detailed analysis of expenditures and their main drivers. With the arrival of innovation and predicted increase of the number of patients partly related to ageing process, control of expenditure must be a priority. The developed tool will help decision makers to monitor the burden of diabetes but also to provide stakeholders with a better understanding of trends and regulating actions. Key messages: Diabetes represents a high proportion of healthcare expenditure in France. With the arrival of innovation and predicted increase of the number of patients partly related to ageing process, control of expenditure must be a priority.